Analysis of consumer behavior in buying instant noodles (case studies in the Bogor City Area) - Mohammad Wartaka; Sumardjono Sumardjono (The Management Journal of Binaniaga, 2020)
This research aims to find out the main attributes consumers consider in instant noodle purchases, and to know their attitudes and behaviors.The data source in this study was obtained from 167 respondents in Bogor City Area.Statistical analysis used in this study includes analysis of multi-attribute models of fishbein, subjective norms and Theory of reasoned action. The result of fishbein analysis is as follows four most important evaluation attribute is the number of flavor variations of 1.56, then ease of obtaining products, product halalness and quick/practical in serving with scores of 1.53, 1.42 and 1.35 respectively.The smallest evaluation value is given to the gift-giving attribute in the sale of 0.59 packs.This illustrates that respondents consider promotional attributes in the form of gifts less important than other attributes.However, the score is still in an important category. From the behavioral model it appears that of the four brands analyzed having a value of B ~ BI positive (greater than zero) this means the consumer behavior for the above brands is good or positive.Indomie has the largest value of 30.58 compared to other brands describing the attitude of consumers inclined to make purchases against larger Indomie.Keywords: Consumer Behavior, Fishbein Analysis, Instant Noodles, Subjective Norm Analysis, Theory of Reasoned Action